Impact of cultivation duration and methods on soil physicochemical properties, ginseng growth, and arbuscular mycorrhizal fungi community structure - Wang, Jinlong; Kan, Zhihui; Zhang, Xiaole; Yang, Boya; Dong, Yuxuan; Wang, Bo; Wang, Chunjuan (Frontiers in Microbiology, 2025)
IntroductionGinseng (Panax ginseng C. A. Meyer) is a widely cultivated medicinal plant valued for its bioactive ginsenosides, which are influenced by soil conditions and microbial interactions. However, the long-term effects of different cultivation durations and methods on soil physicochemical properties, arbuscular mycorrhizal fungi (AMF) communities, and ginsenoside accumulation remain largely unexplored.MethodsThis study investigates the relationships between soil characteristics, AMF community structure, and ginseng quality under different cultivation treatments using high-throughput sequencing, soil property analysis, and canonical correspondence analysis (CCA).ResultsThe results indicate that long-term ginseng cultivation significantly reduces soil moisture, organic matter, and nitrate nitrogen contents. Soil pH initially increased and subsequently declined over the cultivation period, and the contents of phosphorus and potassium elements show a fluctuating downward trend with the increase in cultivation years. AMF community composition varied across cultivation years, with Glomus and Paraglomus dominating in later stages, potentially influencing plant nutrient uptake and secondary metabolite synthesis. CCA shows that nitrate nitrogen, total nitrogen, and total phosphorus are positively correlated with AMF community structure, while soil moisture content is negatively correlated. Additionally, ginsenoside accumulation was significantly affected by cultivation conditions, with AMF interactions likely modulating secondary metabolism.DiscussionThese findings provide valuable insights into microbial-mediated soil health management and offer strategies for optimizing ginseng cultivation practices to enhance plant performance and bioactive compound production.